Shaping the Future Workforce: Students' Perceptions on AI and Human-Centric Technologies in Industry 5.0 - Ferhataj Anxhela; Biçoku Jonida; Memaj Fatmir (Economics and Culture, 2025)
This paper aims to analyse how university students perceive the role of Artificial Intelligence and human-centric technologies in shaping the future workforce within the context of Industry 5.0. By focusing on students as future professionals, the study explores their expectations, ethical concerns, and readiness for AI-driven transformation in a developing country context.